2012
DOI: 10.4103/1947-2714.93386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and desire for body contouring surgery in postbariatric patients in Saudi Arabia

Abstract: Background:Morbid obesity has become a common problem worldwide and as a result the demand for bariatric surgery has increased as well. Most patients develop skin redundancy and sagging at many body parts after major weight loss procedures which increased the demand for body contouring procedures.Aims:The study was to address the prevalence and patient's desire for body contouring procedures.Materials and Methods:A cross-sectional study targeting the postbariatric patients from April 2011 to October 2011 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 16 publications
2
39
1
Order By: Relevance
“…Our observations are consistent with these of other authors in bariatric groups after complex body contouring surgery, especially among the women (1,5).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our observations are consistent with these of other authors in bariatric groups after complex body contouring surgery, especially among the women (1,5).…”
Section: Discussionsupporting
confidence: 83%
“…to Kitzinger, to 47% acc. to While and Mitchel (1). Moreover, no single operation can address the whole-body disfigurements resulting from significant weight loss (18,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that there is a large discrepancy between the number of post bariatric patients requesting body contouring surgery and the number undergoing such surgery (14,15,18,19). The proportion of post bariatric patients who have undergone one or more body contouring procedures vary from 14-47%, of which abdominoplasty is by far the most common procedure (33,36,37). Corresponding figures describing the relationship between requested and performed body contouring surgery for Sweden are lacking.…”
Section: Requesting and Undergoing Body Contouring Surgerymentioning
confidence: 99%
“…According to the literature, 73-85% of post bariatric patient's request body contouring surgery (29,(33)(34)(35)(36). Request for correction of abdominal excess skin was most commonly followed by thighs, chest and arms (33).…”
Section: Requesting and Undergoing Body Contouring Surgerymentioning
confidence: 99%